A simplified texture gradient method for improved image segmentation. Issue 4 (April 2016) - Wang, Qi; Spratling, M.
Abstract Inspired by the probability of boundary (Pb) algorithm, a simplified texture gradient method has been developed to locate texture boundaries within grayscale images. Despite considerable simplification, the proposed algorithm's ability to locate texture boundaries is comparable with Pb's texture boundary method. The proposed texture gradient method is also integrated with a biologically inspired model, to enable boundaries defined by discontinuities in both intensity and texture to be located. The combined algorithm outperforms the current state-of-art image segmentation method (Pb) when this method is also restricted to using only local cues of intensity and texture at a single scale.